1985
DOI: 10.1146/annurev.es.16.110185.001143
|View full text |Cite
|
Sign up to set email alerts
|

Phenological Patterns of Terrestrial Plants

Abstract: The term phenology is derived from the Greek word phaino meaning to show or to appear. Hence, phenology is defined as the study of the seasonal timing of life cycle events. For plants the seasonal timing of such events can be critical to survival and reproduction. In agriculture the most common failure of introduced crops is the inability to adjust to the seasons imposed by the new, environment (68). In the past few years, interest in the ecology and evolution of timing of life cycle events has grown. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
680
3
26

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,292 publications
(764 citation statements)
references
References 222 publications
13
680
3
26
Order By: Relevance
“…Phenological complementarity promotes coexistence in multispecies plant communities (37,38) and is one of the main mechanisms by which species composition influences ecosystem processes such as nutrient capture and primary production (39). In Mediterranean-type ecosystems, plant growth is concentrated in a short growing season, so even small shifts in phenology can disrupt complementarity among species.…”
Section: Discussionmentioning
confidence: 99%
“…Phenological complementarity promotes coexistence in multispecies plant communities (37,38) and is one of the main mechanisms by which species composition influences ecosystem processes such as nutrient capture and primary production (39). In Mediterranean-type ecosystems, plant growth is concentrated in a short growing season, so even small shifts in phenology can disrupt complementarity among species.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that even species that may have evolved traits to increase pollination success still suffer due to competition for pollinator service. Plant species may also evolve flowering phenologies that differ from those of their coflowering competitors, thus increasing their conspecific pollen delivery (11)(12)(13). Although there is greater potential for phenological diversity in tropical (speciesrich) areas due to the potentially long growing season (10), if numerous coexisting clades are diversifying in phenology, there may still be higher competition for pollination in species-rich relative to depauperate floras, regardless of flowering time.…”
Section: Discussionmentioning
confidence: 99%
“…Pollen limitation may decrease as plants evolve traits that reduce reliance on pollinators (e.g., self-compatible breeding systems and vegetative reproduction), attract more specialized pollinators that deliver less heterospecific pollen, or reduce competition for pollinators (e.g., shifts in flowering time) (11). Studies have found that diversity in flowering phenologies and pollinator fauna is indeed higher in species-rich areas (12,13).…”
mentioning
confidence: 99%
“…Phenology is the study of recurring plant, fungi, and animal life cycle stages, especially as they relate to climate and weather (Schwartz 2013). Phenological processes such as developmental stages of plant, fungi, and animal species triggered by accumulated heat, or exceedance of temperature thresholds, can also serve as indicators of seasonal variation and proxies to monitor the biological effect of climate change (Larcher 1983, Rathcke and Lacey 1985, Lantz and Turner 2003. Lantz and Turner (2003:265) introduced and defined the term, TPK, to encompass IK regarding phenology:…”
Section: Introductionmentioning
confidence: 99%